Analisis Faktor yang Mempengaruhi Kejadian Hipertensi pada Lansia di Desa Bambu - Ardiansah, Ardiansah; Nur, Akbar; Dwi Swarjana, I Kadek; Iqra S, Iqra S; Tikirik, Wita Oileri (Yayasan Mandar Indonesia, 2024)
Hypertension has become a major issue not only in Indonesia but also globally, as it is one of the risk factors for non-communicable diseases such as kidney failure, diabetes, stroke, and heart disease. Hypertension particularly affects the elderly, whose bodies become weaker due to a compromised immune system, making them more susceptible to diseases, environmental changes, loss of agility and mobility, and physiological changes. The purpose of this study is to identify the factors influencing the occurrence of hypertension among the elderly in Bambu Village. The research employs a quantitative method with a descriptive correlational approach and a cross-sectional design. A total of 65 respondents were sampled using area sampling techniques. The Chi-square statistical test was used to determine the p-value. The instruments used in this study included a closed-question questionnaire and a needle-based blood pressure monitor (aneroid) with the OneMed brand. The results showed that poor physical activity was observed in 44 respondents (67.7%) with a p-value of 0.037, non-smoking behavior was found in 59 respondents (90.8%) with a p-value of 0.379, good dietary patterns were identified in 61 respondents (93.8%) with a p-value of 0.305, and good coffee consumption habits were noted in 49 respondents (75.4%) with a p-value of 0.383. Additionally, mild hypertension was found in the majority, affecting 27 respondents (41.5%). There is a significant relationship between physical activity and the occurrence of hypertension among the elderly in Bambu Village. Interventions for the elderly and health education on the importance of blood pressure control and healthy lifestyles are necessary.